Candidate gene analysis of osteochondrosis in Spanish Purebred horses. (16th July 2016) - Sevane, N.; Dunner, S.; Boado, A.; Cañon, J.
Summary: Equine osteochondrosis (OC) is a frequent developmental orthopaedic disease with high economic impact on the equine industry and may lead to premature retirement of the animal as a result of chronic pain and lameness. The genetic background of OC includes different genes affecting several locations; however, these genetic associations have been tested in only one or few populations, lacking the validation in others. The aim of this study was to identify the genetic determinants of OC in the Spanish Purebred horse breed. For that purpose, we used a candidate gene approach to study the association between loci previously implicated in the onset and development of OC in other breeds and different OC locations using radiographic data from 144 individuals belonging to the Spanish Purebred horse breed. Of the 48 polymorphisms analysed, three single nucleotide polymorphisms (SNPs) located in the FAF1, FCN3 and COL1A2 genes were found to be associated with different locations of OC lesions. These data contribute insights into the complex gene networks underlying the multifactorial disease OC, and the associated SNPs could be used in a marker‐assisted selection strategy to improve horse health, welfare and competitive lifespan.